2022
DOI: 10.1002/mco2.176
|View full text |Cite
|
Sign up to set email alerts
|

Signaling pathways in the regulation of cancer stem cells and associated targeted therapy

Abstract: Cancer stem cells (CSCs) are defined as a subpopulation of malignant tumor cells with selective capacities for tumor initiation, self‐renewal, metastasis, and unlimited growth into bulks, which are believed as a major cause of progressive tumor phenotypes, including recurrence, metastasis, and treatment failure. A number of signaling pathways are involved in the maintenance of stem cell properties and survival of CSCs, including well‐established intrinsic pathways, such as the Notch, Wnt, and Hedgehog signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 433 publications
0
14
0
Order By: Relevance
“…Aberrant activation of pathways regulating stem cell selfrenewal, such as Notch, Hedgehog (HH), and Wnt, are also pivotal in the tumorigenic potential of CSCs [44]. Dysregulation of these pathways contributes to drive tumor progression [55]. We examined all three signaling pathways and found that Notch signaling was disrupted in GPX2 depletion HNSCC cells, especially NOTCH3.…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant activation of pathways regulating stem cell selfrenewal, such as Notch, Hedgehog (HH), and Wnt, are also pivotal in the tumorigenic potential of CSCs [44]. Dysregulation of these pathways contributes to drive tumor progression [55]. We examined all three signaling pathways and found that Notch signaling was disrupted in GPX2 depletion HNSCC cells, especially NOTCH3.…”
Section: Discussionmentioning
confidence: 99%
“…There are a large number of previous studies on TGF beta signaling pathway. Studies have shown that the TGF-beta signaling pathway has different roles in the different stages of human cancer progression (Manni and Min, 2020;Baba et al, 2022). TGF-beta acts as a cancer suppressor in the initial stage of tumorigenesis (de Caestecker et al, 2000;Zhang et al, 2017;Chandra Jena et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, the complexity of immune cell heterogeneity across cell types poses challenges in precisely understanding CSC-immune cell interactions. Recently, the widespread use of single-cell RNA sequencing has enabled the identification of changing states in both CSCs and immune cells, shedding light on their interactions in different tumor contexts ( Manni and Min, 2022 ). Further investigation is needed to explore the communication among these immune cells within the tumor microenvironment (TME), with the aim of advancing the development of immunotherapies that specifically target cancer stem cells (CSCs) more effectively.…”
Section: Role Of Circrnas In Lung Cancermentioning
confidence: 99%